Weaker Braking Force, A New Marker of Worse Gait Stability in Alzheimer Disease - Cheng, Qianqian; Wu, Mengxuan; Wu, Yuemin; Hu, Yaoyao; Kwapong, William Robert; Shi, Xiang; Fan, Yinying; Yu, Xin; He, Jincai; Wang, Zhen (Frontiers in Aging Neuroscience, 2020)
Background: Braking force is a gait marker associated with gait stability. This study aimed to determine the alteration of braking force and its correlation with gait stability in Alzheimer disease (AD). Methods: A total of 32 AD patients and 32 healthy controls (HCs) were enrolled in this study. Gait parameters (braking force, gait variability, and fall risk) in the walking tests of Free walk, Barrier, and Count backward were measured by JiBuEn® gait analysis system. Gait variability was calculated by the coefficient of variation (COV) of stride time, stance time, and swing time. Results: The braking force of AD was significantly weaker than HCs in three walking tests (P < 0.001, P < 0.001, P = 0.007). Gait variability of AD showed significant elevation than HCs in the walking of Count backward (COVstride: P = 0.013; COVswing: P = 0.006). Fall risk of AD was significantly higher than HCs in three walking tests (P = 0.001, P = 0.001, P = 0.001). Braking force was negatively associated with fall risks in three walking tests (P < 0.001, P < 0.001, P < 0.001). There were significant negative correlations between braking force and gait variability in the walking of Free walk (COVstride: P = 0.018; COVswing: P = 0.013) and Barrier (COVstride: P = 0.002; COVswing: P = 0.001), but not Count backward (COVstride: P = 0.888; COVswing: P = 0.555). Conclusion: Braking force was weaker in AD compared to HCs, reflecting the worse gait stability of AD. Our study suggests that weakening of braking force may be a new gait marker to indicate cognitive and motor impairment and predict fall risk in AD.